Laparoscopic nephrectomy in children for benign conditions: indications and outcome - Prema Menon; Abhilasha T Handu; Katragadda Lakshmi Narasimha Rao; Suman Arora (Wolters Kluwer Medknow Publications, 2014)
Aim: To analyze the indications and outcome of laparoscopic nephrectomy for benign non-functioning kidneys in children. Materials and Methods: The data of all patients operated over a 10 year period was retrospectively analyzed. Results: There were 56 children, aged 4 months to 12 years with a male: female ratio of 2.3:1. The most common presentation in boys and girls was urinary tract infection (UTI) (61.5% and 47.05% respectively). Incontinence due to ectopic ureter was a close second in girls (41.17%). The most common underlying conditions were vesico-ureteric reflux (42.85%) and multicystic dysplastic kidney (23.2%). There were 6 nephrectomies, 4 heminephroureterectomies and the remaining nephroureterectomies. All children tolerated the surgery well. One patient underwent a concomitant cholecystectomy. The post-operative problems encountered were UTI (1), urine retention (1), pyonephrosis in the opposite kidney and development of contra-lateral reflux (1). All others had resolution of pre-operative symptoms with good cosmesis. Conclusions: As per available literature, this appears to be the largest Indian series of pediatric laparoscopic nephrectomies for benign non-functioning kidneys. Laparoscopic approach gives excellent results provided pre-operative investigations rule out other causes for the symptoms with which the patient presents. Often it is not the kidney but the dilated dysplastic ureter which is the seat of stasis and infection or pain and therefore should be completely removed.